2021
DOI: 10.1155/2021/5521516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subacute Exposure of Dibutyl Phthalate on the Homeostatic Model Assessment, Thyroid Function, and Redox Status in Rats

Abstract: Dibutyl phthalate is an endocrine disruptor used in a wide range of industrial and agriculture applications. The present study focuses on elucidating the effect of subacute exposure (4-weeks) of DBP on insulin and its sensitivity indexes, oxidative status, thyroid function, energy metabolites, serum biochemistry, and anthropometry in rats. A total of 64 rats were divided into 4 treatment groups as mg DBP/Kg body weight per day: (a) 0 mg/Kg (control), (b) 10 mg/Kg (DBP-10), (c) 50 mg/Kg (DBP-50), and (d) 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…On the other hand, (Baralić, Živančević, et al, 2021) conducted a toxicogenomic analysis study and reported several genes linked to diabetes type 2 and mutual for BPA and DBP. Also, (Majeed et al, 2021) reported that hyperglycemia and insulin resistance, in rats could be attributed to DBP exposure. Such conflicting results might be explained by different doses, duration, mode of exposure, gender, and the experimental model used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, (Baralić, Živančević, et al, 2021) conducted a toxicogenomic analysis study and reported several genes linked to diabetes type 2 and mutual for BPA and DBP. Also, (Majeed et al, 2021) reported that hyperglycemia and insulin resistance, in rats could be attributed to DBP exposure. Such conflicting results might be explained by different doses, duration, mode of exposure, gender, and the experimental model used.…”
Section: Discussionmentioning
confidence: 99%
“…Also, (Majeed et al, 2021) reported that hyperglycemia and insulin resistance, in rats could be attributed to DBP exposure. Such supported by who reported an additive effect of both BPA and DBP combined in the induction of type 2 diabetes via apoptosis and oxidative stress-mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%